From entity-violence to identity-violence: a study of The Golden Ass, by Apuleius - Santos, Vinicius Medeiros dos [UNESP]; Aquati, Claudio [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
The purpose of this study is to contribute to the investigations about the manifestation of violence in ancient literature, here particularly in Apuleius' ancient Roman novel, presenting an analytical reading of this phenomenon that manifests itself in The Golden Ass, and recognizing and classifying it as an event linked, on one hand, to entity-violence and, on the other hand, to identity-violence.
Keywords: Ancient Roman Novel; Apuleius; The Golden Ass; Violence in literature